Production of Salt Tolerant Ruzi Grass (Brachiaria ruziziensis) by Tissue Culture - Pradit Pongtongkam; Surin Peyachoknagul; Dirida Manawiboon; Jantakarn Arananant; Amara Thongpan; Sayan Tudsri (Agriculture and Natural Resources, 2006)
The best medium formula for multiple shoot induction was determined for seed culture of Ruzi grass (Brachiaria ruziziensis). Murashige and Skoog (MS) medium containing 10 mg/l BAP gave the highest average of 7.49 shoots. These shoots were irradiated at different doses of 0, 10, 30 , 50, and 70 Gy and transferred to grow on the selected multiple shoot induction medium having different concentrations of NaCl at 0, 0.5,1.0, 1.5 and 2.0%. It was found that the percentages of shoot survival decreased as the radiated doses increased. However, at the high salt concentration of 2.0% the growth was completely inhibited. All 173 clones of surviving plant were transferred to grow in the natural field at the National Corn and Sorghum Research Center, Nakhon Ratchasima province. A set of replicated plants from this field was also grown under high saline soil at Borabue district, Maha Sarakham province for comparison. Fifteen healthy clones were chosen from these two sites and grown in the high saline soil for one year. Only ten surviving clones were collected from this second growth and propagated as salt tolerant Ruzi grass. Upon testing the DNA fingerprints of the original 15 healthy clones using AFLP technique with 10 pairs of primers, there was no differences in the banding patterns found among them.